Ex vitro grafting of papaya (carica papaya l.) - Liew, Cai Foon. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Papaya (Carica papaya L. ) is a polygamous fruit crop with three basic sex types i. e. male, female and bisexual. Papaya plants derived from seeds are not genetically true-to-type. Although vegetative propagation can be used to produce papaya with desired sex type but it is not efficient. Therefore, micropropagation by in vitro techniques had been developed to mass propagate papaya. Since rooting efficiency of the tissue-culture derived papaya shoots is still low, micrografting of papaya if successful can serve as an interim measure for production of papaya planting material. The objective of this project is to develop a method for micrografting of papaya ex vitro. Micrografting was done by using in vitro shoots as scions and papaya seedlings as rootstocks. The seedlings were used as rootstocks when they reached 2-3 cm height in in vitro grafting. The in vitro shoots had undergone three subcultures in modified DS media supplemented with 0.5 mg/L BAP and 0.2 mg/L NAA before transferred to media containing 0.5 mg/L GA3 for shoot elongation. The shoots were used as scions when they reached 1-1.5 cm height. The grafting procedures were carried out both in vitro and ex vitro. Two grafting methods i. e. wedge and saddle grafting had been tried. Wedge grafting was found to be more successful than saddle grafting.